LAW ENFORCEMENT OF THEFT WITH VIOLENCE RESULTING IN DEATH BASED ON THE PERSPECTIVE OF JUSTICE - Widyatama, Alfian; Sujono (International Peneliti Ekonomi, Sosial dan Teknologi, 2025)
Law enforcement must be carried out fairly and without discrimination in order to create justice and order in society. This study discusses law enforcement against the crime of theft with violence resulting in death based on Article 365 paragraph (3) of the Criminal Code, as well as an analysis of the legal considerations of judges in District Court Decision Number 33/Pid.B/2024/PN.Llg. The method used is normative juridical research with the approach of legislation and decision studies. The results showed that the perpetrator was sentenced to a maximum imprisonment of fifteen years as a form of fair law enforcement. The judge's consideration includes the fulfillment of the elements of the article charged, the demands of the public prosecutor, and the absence of reasons for criminal erasure. Law enforcement in the decision is in accordance with the principles of justice, certainty, and legal benefits. Therefore, law enforcement in the future must refer to the applicable rules of law in order to provide a deterrent effect, as well as protection and security for the community.